The Influence of Binahong (Anredera cordifolia) Leaf Powder Addition to Feed on the Prevalence and Survival Rate of Red Tilapia (Oreochromis niloticus) seeds Infected by Aeromonas hydrophilla Bacteria - Juliana Juliana; Yuniarti Koniyo; Citra Panigoro (Journal Omni-Akuatika, 2020)
Feed is one main factor in aquaculture activities which influences the quantity and quality of aquaculture commodities. Feed can also increase the cultivated fish survivability to prevent from fish diseases. Binahong leaf powder is one material added in the fish feed making which contains active compounds functioning as antibacterial agent. This study did aim at examining the influence of Binahong leaf powder addition to feed on the prevalence and survival rate of Red Tilapia seeds infected by Aeromonas hydrophila bacteria. This research employed an experimental method using a randomized complete design with four treatments. Each treatment consisted of different Binahong leaf powder dosage used as the material in feed making with treatment A (5%), treatment B (7%), treatment C (9%), and treatment D (control). The test animals were ± 5 cm red tilapia seeds infected by Aeromonas hydrophila bacteria. Feeding was given twice, in the morning and evening with the feeding rate of 10% per day of the total body weight. The research results showed that the addition of Binahong leaf powder did not influence the prevalence and survival rate of red tilapia seeds infected by Aeromonas hydrophila bacteria. Keywords: Aeromonas hydrophila, Bacteria, Binahong, Disease, Feed